Computational approaches for understanding energy metabolism. (29th July 2013) - Shestov, Alexander A.; Barker, Brandon; Gu, Zhenglong; Locasale, Jason W.
<x xml:space="preserve">Abstract</x> There has been a surge of interest in understanding the regulation of metabolic networks involved in disease in recent years. Quantitative models are increasingly being used to interrogate the metabolic pathways that are contained within this complex disease biology. At the core of this effort is the mathematical modeling of central carbon metabolism involving glycolysis and the citric acid cycle (referred to as energy metabolism). Here, we discuss several approaches used to quantitatively model metabolic pathways relating to energy metabolism and discuss their formalisms, successes, and limitations. WIREs Syst Biol Med 2013, 5:733–750. doi: 10.1002/wsbm.1238 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.